The alphabet : how Pine Cone and Pepper Pot (with the help of Tiptoes Lightly and Farmer John) learned Tom Nutcracker and June Berry their letters - Down, Reg, 1954- ([Sacramento, Calif.] : [Lightly Press], 2014)
Summer is almost over and Tom Nutcracker is soon to go to school. But deep in the forest on his father's farm two gnomes called Pine Cone and Pepper Pot are worried. What if the school does not teach Tom his letters properly? What if the teacher messes the alphabet up?
Keywords: Alphabet -- Juvenile fiction; Gnomes -- Juvenile fiction